Current status of sentinel lymph node mapping in the management of endometrial cancer. (January 2013) - Robova, Helena; Rob, Lukas; Halaska, Michael Jiri; Pluta, Marek; Skapa, Petr
The prognosis of endometrial cancer (EC) is generally favorable, while lymph node status remains the most important prognostic factor. Sentinel lymph node mapping (SLNM) could help to find women in whom adjuvant therapy could be omitted. This review analyzes different techniques of injection and histopathologic elaboration of SLNM in EC. Results of studies on SLNM in ECs seem to be promising, but only a small series have been published so far. The studies are subdivided into three groups by the technique of injection (hysteroscopic, subserosal and cervical). Range of detection rate for SLNM varies from 45 to 100%. Hysteroscopic injection is not easy to learn; moreover, exact peritumoral injection in large tumors is often impossible. Subserosal administration of tracer is difficult during laparoscopic or robotic surgery. Cervical injection is quite a controversial technique because distribution of SLNs in ECs is different from cervical cancer; moreover, there is no large study using cervical injection with systematic pelvic and para-aortic lymphadenectomy.